SISTEM INFORMASI MANAJEMEN DISTRIBUSI STUDI KASUS PT ARDERAMA MANDIRI - Dani Pradana Kartaputra; Herna Gunawan; Naufal Sidqi Novian (Jurnal Teknologi Informasi dan Komunikasi, 2022)
PT. Arderama Mandiri is a company engaged in distribution and importation, handling printed goods, office equipment, musical instruments, computer accessories, software, and more. Since 2011, the company's delivery scope has expanded significantly. With the increasing number of consumers placing orders, the company has encountered issues such as customer complaints about long delivery times and difficulties in the warehouse department with monitoring deliveries. To address these challenges, it is necessary to develop a system that can effectively monitor the distribution of goods. The Website-based Distribution Management Information System is designed using the waterfall Software Development Life Cycle (SDLC) method, which includes six stages: System Engineering, Analysis, Design, Coding, Testing, and Maintenance. This approach involves analyzing the problem with Unified Modeling Language (UML), designing a solution in the form of a wireframe for the information system, and then proceeding to the Coding stage where the system is built using PHP and the Laravel framework.